2018
DOI: 10.1111/ced.13378
|View full text |Cite
|
Sign up to set email alerts
|

Depression- and anxiety-like behaviour is related to BDNF/TrkB signalling in a mouse model of psoriasis

Abstract: BDNF/TrkB signalling participates in the pathological mechanism of depression and anxiety behaviours in psoriasis. Our findings provide a new therapeutic strategy for the treatment of skin lesions in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
(36 reference statements)
2
17
3
Order By: Relevance
“…Our data showed that these DEGs were mainly enriched in the neurotrophin signaling pathway, insulin signaling pathway, alcoholism, GABAergic synapse, glutamatergic synapse, amphetamine addiction, MAPK signaling pathway, PI3K‐Akt signaling pathway and circadian rhythm (Table ). Interestingly, these signaling pathways are involved in the pathophysiology and treatment of depression . For example, GABA and glutamate neurotransmitter deficits are used to explain the neurobiological abnormalities associated with MDD, which has been well‐accepted .…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that these DEGs were mainly enriched in the neurotrophin signaling pathway, insulin signaling pathway, alcoholism, GABAergic synapse, glutamatergic synapse, amphetamine addiction, MAPK signaling pathway, PI3K‐Akt signaling pathway and circadian rhythm (Table ). Interestingly, these signaling pathways are involved in the pathophysiology and treatment of depression . For example, GABA and glutamate neurotransmitter deficits are used to explain the neurobiological abnormalities associated with MDD, which has been well‐accepted .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that fluoxetine improves BDNF expression and concentration (35)(36)(37). Some studies have shown that BDNF expression induced by fluoxetine is associated with BDNF-TRKB signalling (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells may have a significant role in depression, while high levels of IL17 and IL17A high levels could be involved in psoriasis-associated depression [15,16,17] . In a mouse psoriasis model, the antidepression and anti-anxiety drug-fluoxetine, significantly contributed to improvement [18] .…”
Section: Introductionmentioning
confidence: 99%